If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19x + -4(5x + -8) = 36 Reorder the terms: 19x + -4(-8 + 5x) = 36 19x + (-8 * -4 + 5x * -4) = 36 19x + (32 + -20x) = 36 Reorder the terms: 32 + 19x + -20x = 36 Combine like terms: 19x + -20x = -1x 32 + -1x = 36 Solving 32 + -1x = 36 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-32' to each side of the equation. 32 + -32 + -1x = 36 + -32 Combine like terms: 32 + -32 = 0 0 + -1x = 36 + -32 -1x = 36 + -32 Combine like terms: 36 + -32 = 4 -1x = 4 Divide each side by '-1'. x = -4 Simplifying x = -4
| 2x+5x-1= | | 2n+3=4.4 | | (x+8)(x+4)=42 | | -5=5/6t-1/2 | | 1-5/x=14/x^2 | | 7x-12=2(x+6) | | 13=0.06s | | 2-b/3=-4.5 | | 8b-2a+5b+6a= | | (y*y+4)-(y-2*8)= | | 7y+x=-2 | | c=2.54i+5 | | 7/3-11/12x=7/4 | | 1-4b+b=-14 | | 5+-7=N | | (X-2)*(x-2)-14=2 | | 2.5x+6-2.5x=5.7x-10-2.5x | | (y*y+4)-(y-2*4)= | | -14=3v+4v | | 7/2-5/6x=4/3 | | y*y+4-y-2*4= | | 2n-10=4n+18 | | 14x+26=180 | | 6x-5=16x-15 | | (x+1)*(x+1)=4 | | 10x-7=6x-1 | | 7x-10=-6 | | 5X-13X=N | | x^2+2x=38 | | -2u=-5.52 | | y*y+4-8*y-2= | | 8n-10=2(4n-5) |